2014
DOI: 10.5455/bcp.20131218094342
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Impulsivity and Aggression at a 12-Month Follow-Up Among Male Heroin Dependent Patients

Abstract: Eroin bağımlısı erkek hastaların 12 aylık izleminde dürtüsellik ve agresyon şiddeti Amaç: Bu çalışmanın amacı hastaneden taburcu olduktan 12 ay sonra halen idame tedavisi olarak buprenorfin/nalokson kullanan hastalar ile depreşen hastaların dürtüsellik ve agresyon puanlarındaki değişimi incelemekti. Yöntem: Ardışık olarak kliniğe yatışı yapılan 78 erkek eroin bağımlısı hastadan 52'si taburculuktan 12 ay sonra yüz yüze görüşme ile değerlendirildi. Hastalara hem başlangıçta hem de 12 ayın sonunda Barrat Dürtüsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Studies investigating the relationship between level of anger and substance addiction reveal that there is a strong relationship between substance use and anger. [8][9][10] Studies suggest that as the level of anger increases, the negative effect of substance use on quality of life and also desire of substance increase. Level of anger is one of the important factors to be investigated and handled in the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the relationship between level of anger and substance addiction reveal that there is a strong relationship between substance use and anger. [8][9][10] Studies suggest that as the level of anger increases, the negative effect of substance use on quality of life and also desire of substance increase. Level of anger is one of the important factors to be investigated and handled in the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is data obtained from a few randomized clinical trials related to overall effectiveness of BN tablets in the treatment of opiate dependence, there is relatively limited study related to efficiency and reliability of the maintenance treatment which reflects real world conditions 17 . Also, there are fewer studies which were reported the efficacy of BN on opiate dependence in Turkey 18,19 . In this study, we aimed to determine the efficacy of BN maintenance therapy in patients with opiat dependence by evaluating the rate of treatment continuation, the perceived stress level, functionality, craving, and quality of life.…”
Section: Introductionmentioning
confidence: 99%